Investigation of Noise and Resolution of Magnetic FinFET (MAG-FinFET) - Khine Thandar Nyunt Swe; Amporn Poyai; Toempong Phetchakul (IEEE Sensors Journal, 2024)
FinFET has become a potential candidate to overcome the problem of the short-channel effect and is applicable as magnetic FinFET (MAG-FinFET) in the magnetic sensor industry. MAG-FinFET based on the current mode operation of the Hall effect is designed by creating two drain contacts at the sidewalls of the device to detect the vertical magnetic field and its resolution is estimated from the study of noise analysis. To investigate noise and resolution of the MAG-FinFET, a small-signal ac analysis simulation is performed in Sentaurus TCAD. Diffusion noise, monolithic generation recombination noise, and flicker generation recombination noise are applied as the local noise sources, and the noise outputs of MAG-FinFET are obtained as the noise power spectral density. At the lower frequency, flicker recombination noise dominates, while the diffusion noise prevails at higher frequency. The sensitivities of MAG-FinFET are compared under the two situations without the application of noise and with the consideration of noise. Source current, drain voltage, and gate voltage are varied to understand their effect on the sensitivity and noise. The source current $1.25~\mu $ A gives the highest absolute sensitivity and the lowest noise levels compared to other source currents. The drain and gate voltages of 1.2 V bring the highest noise spectral densities among other drain and gate voltages. For the resolution of nanoscale MAG-FinFET, the minimum detectable magnetic field is evaluated from the sensitivity and noise current spectral density. The minimum detectable magnetic field ${B}_{\min }$ is 130 mT/ $\surd $ Hz at the frequency of 1 Hz for a narrow bandwidth, and for a widebandwidth, the equivalent magnetic field ${B}_{\text {eq}}$ at the frequency of 100 Hz is obtained as 342 mT/ $\surd $ Hz.
Keywords: Magnetic Field Sensors Techniques; Neural Networks and Applications; Non-Destructive Testing Techniques